Assessing the representativeness of online job advertisements - Joanna Napierała; Vladimír Kvetan; Jiri Branka (Publications Office of the European Union, 2022)
This working paper presents results of an assessment of the representativeness of information collected from online job advertisements (OJA) in establishing the number of labour market vacancies in EU Member States. Two external data sources were used, Labour force survey (LFS) and Job vacancies survey (JVS), available in most EU countries. The coverage biases in OJA data, in comparison to existing data sources, are evaluated at sectoral, occupational and geographic levels.
Keywords: 370; Personalbeschaffung; Anforderungsprofil; Online-Marketing; Offene Stellen; Datenerhebung; Statistische Daten; EU-Staaten